INCURSION OF KNOWLEDGE MANAGEMENT IN MANAGEMENT EXCELLENCE AWARDS: AN ANALYSIS IN THE LATIN-AMERICAN CONTEXT - Resende Junior, Pedro Carlos; Reis, André Luiz Nascimento (Brazilian Journal of Operations & Production Management, 2016)
The aim of this article is to describe the relationship between theoretical knowledge management assumptions and knowledge management process involving Models and Awards for Management Excellence in Latin America. Relevant literature was reviewed by carrying out a survey based on document analysis involving requirement of models and awards for excellence in management in the following countries: Argentina, Brazil, Chile, Colombia and Mexico. This research study used qualitative data-collecting methods by means of a content analysis technique, carried out between February 2013 and December 2014. The corpus was treated by using a content analysis technique, where categories of analysis were codified based on criteria, items and management process requirements of the models investigated. The findings show that the mains theoretical knowledge management assumptions are present, in some degree, in models of management excellence in Latin America, but highlight the fact that these models present different structure and maturity levels, some of which combine knowledge management with strategic perspectives and innovation management. This survey made it possible to produce consistent analyses based on pre-existing models that consider knowledge management as the basis of organization.